Movement behavior of rock strata in multi-level sublevel filling mining and forecasting of differential surface subsidence - Fei Li; Yihui Feng; Haitao Ma; Yongming Yin; Xinai Lu; Chaoyu Zan (Results in Engineering)
To address issues such as ground pressure manifestation, rock beam fracture, and overburden displacement caused by multi-level sublevel filling mining of gently inclined medium-thick ore bodies, this study adopts the Fankou Lead-Zinc Mine as the engineering background. Through a combination of numerical simulation and theoretical analysis, it systematically reveals the movement behavior and the mechanism of surface subsidence of the overburden under the disturbance of multi-level sublevel filling mining. Mechanical models of the stress “pressure relief arch” and “bearing arch” are established, along with a mechanical model of the filling body and roof under combined disturbance effects. The results indicate that multi-level sublevel filling mining induces nonlinear superposition effects in the stress unloading-loading cycles. The disturbance of adjacent stopes induces an alternating development pattern of “pressure relief arch” and “bearing arch”. The activation of potential slip surfaces under combined disturbance is a key controlling factor contributing to asymmetric surface settlement. The disturbance zone can be divided into three types: a direct disturbance zone influencing the settlement magnitude of the overburden; a compound disturbance zone that alters the transmission pattern of mining-induced stress and the height of the stress arch; and a potential slip zone prone to shear and tensile failure. The stope layout pattern significantly influences the transmission pattern of mining-induced stress and the disturbance range. Under the intermittent mining mode, the overburden experiences uneven deformation within a height range of less than 150 m, whereas under the continuous filling-mining mode, uneven deformation extends to a height of up to 220 m.